2017
DOI: 10.1002/acr.23121
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Biochemical Markers of Bone Turnover and Bone Changes on Imaging: Data From the Osteoarthritis Initiative

Abstract: Objective To determine the relationship between biochemical markers involved in bone turnover and bone features on imaging in knees with osteoarthritis (OA). Methods We analysed data from the OA Biomarkers Consortium within the Osteoarthritis Initiative (n=600). Bone marrow lesions (BMLs), osteophytes, subchondral bone area (mm2) and shape (position on 3D vector) were assessed on MRIs and bone trabecular integrity (BTI) was assessed on radiographs. Serum (s) and urinary (u) markers (sCTX-I, sNTX-I, uNTX-I, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Changes in bone remodeling are frequently present early in the OA process 7 . Using data of the Osteoarthritis Initiative, association between serum (S) and urine (U) biochemical markers of bone turnover and bone features on magnetic resonance images (MRI) was evaluated.…”
Section: Predictors Of Oa Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in bone remodeling are frequently present early in the OA process 7 . Using data of the Osteoarthritis Initiative, association between serum (S) and urine (U) biochemical markers of bone turnover and bone features on magnetic resonance images (MRI) was evaluated.…”
Section: Predictors Of Oa Progressionmentioning
confidence: 99%
“…Using data of the Osteoarthritis Initiative, association between serum (S) and urine (U) biochemical markers of bone turnover and bone features on magnetic resonance images (MRI) was evaluated. Although at baseline, most biomarkers, in particular urinary C-telopeptide of type II collagen (uCTX-II), were associated with bone marrow lesions (BMLs), the markers were not predictive of changes in BMLs or osteophytes at follow-up 7 . Serum biomarkers of synovial inflammation, MMP-3 and hyaluronic acid (HA), were associated with moderate to large effusion MRI-detected synovitis; but there was no association between the markers and changes in MRI features of synovitis (Hoffa and effusion synovitis) 8 .…”
Section: Predictors Of Oa Progressionmentioning
confidence: 99%
“…Specific bone biomarkers (sCTX-I, sNTX-I, uNTX-I, uCTX-II, uCTX-Ia/b) were tested by the consortium in 600 OAI participants' serum and urine for associations with bony features on imaging, at baseline and over 24 months 14 . Most markers were associated with baseline bone marrow lesions (BMLs); uCTX-II was also associated with large osteophytes (OR 1.39 [1.10, 1.77]) and bone shape.…”
Section: Progress In Qualified Oa Biomarkersmentioning
confidence: 99%
“…Using the same FNIH cohort, Hunter et al. showed that bone shape was associated with radiographic and pain progression longitudinally 6 , while imaging biomarkers of bone (including bone shape and BML measures used in this study) were only weakly associated with OA biochemical biomarkers; however bone shape and BMLs were not directly compared 11 . In the same cohort, Collins et al.…”
Section: Discussionmentioning
confidence: 68%